Implementing innovative technology promoting self-awareness of brain health and self-determination in obtaining a timely dementia diagnosis: protocol for a multimethods, concurrent, two-part observational study - Sharon L Naismith; Helen Macpherson; Bernice Redley; Alison M Hutchinson; Lidia Engel; Liliana Orellana; Loren Mowszowski; Tanita Botha; Tracey K Bucknall; Rajesh Vasa; Kon Mouzakis; Eva Yuen; et al. (BMJ Open)
Introduction Diagnosis in the early stages of dementia can lead to successful delay in associated cognitive decline. However, up to 76% of Australians diagnosed with dementia have already advanced beyond the early stage of disease. BrainTrack is an evidence-based mobile application (app) designed in Australia to promote brain health self-awareness, self-determination to promote help-seeking and, ultimately, a timelier dementia diagnosis. We will evaluate user experience, implementation and social return-on-investment outcomes of BrainTrack and will report dementia-related concerns, dementia literacy, knowledge, stigma and motivation for behaviour change and explore their associations with demographic characteristics.Methods and analysis A multimethods, concurrent, two-study observational design will be used. Study 1 will evaluate BrainTrack user experience and implementation outcomes, changes in users’ dementia literacy, dementia knowledge, perceptions of dementia-related stigma and help-seeking at five time points (baseline, 1, 3, 6 and 12 months). People residing in all states and territories of Australia will be recruited to the study via the BrainTrack app. Data collection will occur online and through teleconferencing. Approximately 1000 participants will complete all five surveys. Google Analytics data will measure adoption. App usage data will identify app use patterns. A sample of continuing app users (~n=80) and those who cease app use within 6 months (~n=20) will be interviewed to obtain in-depth information about their app use and help-seeking experience. Dementia Australia Helpline data will quantify help-seeking calls triggered by BrainTrack use. In Study 1, longitudinal outcomes will be analysed using mixed models. The economic and social value of BrainTrack will be assessed using social return on investment analysis. In Study 2, general practitioners (~n=20) currently practising in Australia will participate in semi-structured interviews conducted via online teleconferencing. Interviews will elicit perceptions of the usefulness of BrainTrack for initiating and facilitating discussions with patients about cognition and dementia. Qualitative data will be analysed thematically, followed by deductive analysis guided by the Theoretical Domains Framework.Ethics and dissemination This study has received Human Research Ethics Committee approval from Deakin University Human Research Ethics Committee (Study 1: HREC Reference Number 2022–220) and Deakin University Human Ethics Advisory Group, Faculty of Health (Study 2: Reference Number 202_2022). Informed consent will be obtained prior to participation, either verbally for interviews or online for surveys. Study findings will be published in peer-reviewed journals and communicated to key stakeholders.